SISTEM PERINGATAN DINI SERANGAN HAMA PENYAKIT PADI DI JAWA TENGAH MENGGUNAKAN GI DAN GI* STATISTIC - Prasetyo, Sri Yulianto Joko (JURNAL ILMIAH MATRIK, 2015)
Abstract: The research aims to develop the early warnung system application of the endemic areas of pest using Gi and Gi * statistic methods. The research focused on developing early warning system based Geograpical Information System (GIS) technology. The research was conducted through two stages: (1) data preprocessing based on the local characteristics of the studied areas, processing and modeling the data including the digitalization process of cumulative pest area attack using database and (2) architectural design and develop of GIS application. Developing of GIS application using PHP Programming and MapServer. The result of the research showed it can be used to provide information of endemic areas in the future based on the indicator of attack pest. The result of the research could be developed as decission support tool to determine of the endemic pest areas which has been done by observation center for Pest Plant Diseases Laboratory Observations Region V Surakarta, Central Java, Indonesia, Ministry of Agriculture, Republic of Indonesia for many times. Keywords: Getis Ord, GIS, Pest Outbreak, Early Waning System